Protesting Parties in Europe: A comparative analysis. (September 2021) - Borbáth, Endre; Hutter, Swen
The article provides the first large-scale study of protest activities by political parties. The empirical analysis draws on original protest event data for 30 European countries based on semi-automated coding of news agencies. The article innovates by (a) proposing a standardized indicator for the extent to which protest and electoral politics relate to each other, (b) showing that parties' involvement in protests differs across political contexts, and (c) mapping the profile of a typical party-sponsored event and a typical protesting party. Despite long-term trends toward differentiated modes of interest intermediation, the results indicate that a wide range of parties does protest. However, in highly differentiated contexts, the typical protesting party mirrors the outsider image of movement parties: it does not belong to a mainstream party family and has no government experience. By contrast, more strategic factors, such as opposition status, drive parties to the streets in less differentiated contexts.